Vegetation Degradation As A Result Of Tourism Development At The Sumber Sirah Natural Sacred Site Forest, Malang - Purnomo, Purnomo; Batoro, Jati; Riniwati, Harsuko; Leksono, Amin Setyo (Journal of Indonesian Tourism and Development Studies, 2023)
Natural sacred sites are areas that possess cultural and spiritual significance within the community. The village forest around the Sumber Sirah is a natural sacred site. Currently, part of the forest area has changed its function to become a tourist area integrated with spring tourism. This may lead to changes in the structure and composition of the vegetation in the area. The purpose of this study was to analyze the structure of the vegetation composition between natural and changed vegetation for tourism activities. This research was conducted in Putukrejo Village, Gondanglegi District, Malang Regency, East Java. Data collection was carried out by making 20 x 20 m2 sample plots for vegetation that has a tree habitus. 10 x 10 m2 for pole habitus, 5 x 5 m2 for sapling habitus, 2 x 2 m2 for seedling habitus and herb/ground cover. The results of the vegetation analysis then determine the importance value index (IVI), Shannon-Weiner index (H'), evenness index (E'), dominance index (id), and endemism (End). Based on the research results, the composition of plants differs between natural areas and tourist areas. Specifically, 35 species were identified in the natural area, while 20 species were found in the tourist area. The value of endemism in areas that are still natural for all habitus is in the high category, where the vegetation composition is generally found in lowland forests. In contrast, the composition of tourist areas is dominated by cultivated plants and some introduced species. The Shannon-Wiener diversity index, both natural and tourist, is in the moderate category. The evenness index falls within the moderate to high category, and the dominance index is classified as high.